Culture, History and Story: a case study in late medieval Valencia - Calvé Mascarell, Óscar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Academic demands from several disciplines (History, Philology, Art History…) set boundaries of contents diverging from experience in a given period, when such limits did not exist. This paper deals with an innovative teaching experience, following a methodological approach inspired by Paul Zumthor’s medieval triangle of expression. A strategy is devised to present history of culture related to two very relevant characters in late medieval Europe, Vincent Ferrer (c. 1350-1419) and Bonifacio Ferrer (c. 1355-1417).